2015
DOI: 10.3389/fnbeh.2015.00030
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine receptors mediating sensorimotor gating and its enhancement by systemic nicotine

Abstract: Prepulse inhibition (PPI) of startle occurs when intensity stimuli precede stronger startle-inducing stimuli by 10–1000 ms. PPI deficits are found in individuals with schizophrenia and other psychiatric disorders, and they correlate with other cognitive impairments. Animal research and clinical studies have demonstrated that both PPI and cognitive function can be enhanced by nicotine. PPI has been shown to be mediated, at least in part, by mesopontine cholinergic neurons that project to pontine startle neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 72 publications
(107 reference statements)
1
8
1
Order By: Relevance
“…An additional potential factor that could have affected to the data from the schizophrenia patients is related to the elevated proportion of smokers in our sample (close to 80%). However, it has been demonstrated that nicotine increases PPI in healthy humans (e.g., Della Casa et al, 1998 ), in schizophrenia patients (e.g., Hong et al, 2008 ), and in rodents (e.g., Pinnock et al, 2015 ), but our data indicates that PPI was reduced for the Schizophrenia patient’s sample. Therefore, we can discard an effect of the smoking status on our results.…”
Section: Discussioncontrasting
confidence: 87%
“…An additional potential factor that could have affected to the data from the schizophrenia patients is related to the elevated proportion of smokers in our sample (close to 80%). However, it has been demonstrated that nicotine increases PPI in healthy humans (e.g., Della Casa et al, 1998 ), in schizophrenia patients (e.g., Hong et al, 2008 ), and in rodents (e.g., Pinnock et al, 2015 ), but our data indicates that PPI was reduced for the Schizophrenia patient’s sample. Therefore, we can discard an effect of the smoking status on our results.…”
Section: Discussioncontrasting
confidence: 87%
“…Swerdlow et al 2008). Of course, these various drug effects might reflect sites of action anywhere from the PFC (Swerdlow et al 2012a, b) to the pons (Pinnock et al 2015) that might be more or less relevant to the ability of a drug to enhance the therapeutic impact of a cognitive therapy.…”
Section: Drug-enhanced Ppi As a Biomarker For Pact?mentioning
confidence: 99%
“…In addition, α7 nAChRs of the hippocampus and cortex also play important roles in cognitive function in norm and pathology [29,30,[36][37][38][39], and there is evidence of a relationship between PPI and cognitive disturbances in patients with schizophrenia [9,10,40]. There are also single direct data that α7 nAChRs selectively mediate the stimulating effect of nicotine and other selective agonists on PPI [41,42].…”
Section: Introductionmentioning
confidence: 99%